Caffeic Acid Induces Intrinsic Apoptotic Pathway in MG-63 Osteosarcoma Cells Through Bid Truncation and Cytochrome c Release - Ferry Sandra; Muhammad Ihsan Rizal; Ayasha Hajjar Audreyandra Wahid; Monica Andajana; Maria Celinna (The Indonesian Biomedical Journal, 2022)
BACKGROUND: Caffeic acid has been reported to induce apoptosis in MG-63 osteosarcoma cells via caspases activation. However, apoptotic pathway that is involved in the caffeic acid-induced apoptosis is still unclear. Present study aimed to investigate the role of cytochrome c (Cyt c) release and BH3-interacting death (Bid) activation in caffeic acid-induced apoptosis in MG-63 osteosarcoma cells.METHODS: MG-63 cells were cultured, pretreated with/without Z-VAD FMK and treated with/without 10 μg/mL caffeic acid. Treated MG-63 cells were then lysed, homogenized, and processed further to prepare cell lysate and mitochondrial fraction. Immunoblotting method was used to measure the amount of Bid and truncated Bid (t-Bid) as well as mitochondrial and cytosolic Cyt c.RESULTS: The amount of Bid and mitochondrial Cyt c in MG-63 cells decreased in a time-dependent manner, while the amount of t-Bid and cytosolic Cyt c increased in a time-dependent manner. By pretreatment of 100 μM Z-VAD-FMK for 2 h, the amount of Bid and mitochondrial Cyt c was significantly higher, while the amount of t-Bid and cytosolic Cyt c was significantly lower after caffeic acid treatment for 6 and 12 h compared to MG-63 cells that were not pretreated.CONCLUSION: Caffeic acid could induce Cyt c release through the activation of Bid in MG-63 osteosarcoma cells.KEYWORDS: caffeic acid, osteosarcoma, MG-63 cells, Bid, t-Bid, cytochrome c, Z-VAD-FMK